2023
DOI: 10.1177/03000605231168033
|View full text |Cite
|
Sign up to set email alerts
|

The impact of metformin on survival in diabetes patients with operable colorectal cancer: A nationwide retrospective cohort study

Abstract: Objective To investigate the impact of metformin on survival of diabetic patients following surgery for colorectal cancer (CRC). Methods This was a retrospective cohort study. From Taiwan’s population-based National Health Insurance Research Database (NHIRD) we identified 12,512 patients with CRC and type II diabetes who underwent curative surgery between 2000 and 2012. Of these, 6222 patients were included in a matched cohort. Using Cox regression models with time-dependent covariates we examined the impact o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Metformin-derived antineoplastic effects are also mediated by suppression of tumor growth factor (TGF)-β/Inhibin Subunit βA (INHBA) signaling with downregulated cyclin D1 expression and cell cycle inhibition [177], along with urea cycle suppression and reduced putrescine levels [178]. A retrospective study in CRC diabetic patients reported a metformin-mediated survival benefit and reduced risk of liver metastasis after surgery [179]. Metformin induced caspase 3-independent apoptotic death in HCT116 and SW620 CRC cells [180] and disrupted the immunosuppressive effect of the tumor microenvironment [181].…”
Section: Pharmacotherapymentioning
confidence: 99%
See 1 more Smart Citation
“…Metformin-derived antineoplastic effects are also mediated by suppression of tumor growth factor (TGF)-β/Inhibin Subunit βA (INHBA) signaling with downregulated cyclin D1 expression and cell cycle inhibition [177], along with urea cycle suppression and reduced putrescine levels [178]. A retrospective study in CRC diabetic patients reported a metformin-mediated survival benefit and reduced risk of liver metastasis after surgery [179]. Metformin induced caspase 3-independent apoptotic death in HCT116 and SW620 CRC cells [180] and disrupted the immunosuppressive effect of the tumor microenvironment [181].…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Glucose homeostasis enhancement [152,153,155] Inhibition of prediabetes to DM progression [152,153] Increase in GLUT4 expression levels [157] Promotion of GLUT4 membrane translocation [157] Reduction in systemic inflammation and oxidative stress and miR-195 and miR-27 [158] SIRT6 upregulation [159] SGLT2 downregulation [159] Leptin/adiponectin ratio reduction [159] Overall and disease-free CRC survival increase Reduced liver metastasis [174,175,179] Inhibition of mTOR and PI3K/Akt signaling [176,183] AMPK activation [97,176,183] TGF-β/INHBA signaling suppression [177] CyclinD downregulation [177] Urea cycle suppression [178] Reduced putrescin levels [178] Caspase 3-mediated apoptosis [180] Disruption of tumor-mediated immunosuppression [181][182][183] Chemosensitivity increase [97,184]…”
Section: Metforminmentioning
confidence: 99%